Effects of cytokinins and triiodobenzoic acid on in vitro culture of Bauhinia purpurea L. (Botanica Orientalis: Journal of Plant Science, 2019)
Bauhinia purpurea L. is a moderate-sized tree with multipurpose value. The main objective of this study was to evaluate the effects of different cytokinins on growth parameters and develop a standard protocol for nodes and shoot proliferations of B. purpurea. The cytokinins used in this study were 0.5 μM 6-benzylaminopurine (BAP), 5.0 μM 6-(4-Hydroxy-3-methyl-trans-2-butenylamino)-purine (Zeatin) and 5.0 μM N-benzyl-9(2-tetrahydropyranyl)-adenine (BPA), and these were combined with 1.0, 2.0 and 5.0 μM of 2,3,5-triiodobenzoic acid (TiBA). MS medium was used for the experimental purpose. Multiplication rate of plants was recorded after 8 weeks of culture. Best grown plants were acclimatized and stabilized well by natural rooting. Among the combinations, 1.0 μM TiBa and 5.0 μM BPA exhibited the best results in terms of multiplication of nodes, elongation of shoots and length and breadth of calli, thus this combinations can be used for propagation of B. pupurea for large scale multiplication.